A Hauntological Reading of Daphne du Maurier’s “Rebecca” - Nil Korkut-Nayki (English Studies at NBU, 2021)
This essay focuses on the way the main characters in Daphne du Maurier’s novel Rebecca (1938) cope with the haunting influence of the past and attempts to read their struggle through the theoretical approach developed by Jacques Derrida in his Specters of Marx (1993). This approach, termed “hauntology” by Derrida himself, revolves around the notion of the “specter” haunting the present and emphasizes the need to find new ways of responding to it, especially because of the existing ontological failure to do so. The essay complements this reading with the earlier comparable theory of the “phantom” and “transgenerational haunting” developed by psychoanalysts Nicolas Abraham and Maria Torok. A “hauntological” reading of Rebecca through these tools yields results that are significantly different from traditional approaches. Suggesting that the main characters in Rebecca are complete failures in dealing with the specter in a Derridean sense, the essay argues that the novel expects from the discerning reader a more insightful approach and a better potential to understand the specter. It is suggested further that a proper acknowledgement of the specter in Rebecca reaches beyond this particular novel, having subtle but significant implications concerning not only literary analysis but also social and cultural prejudices.